A knowledge-based framework for automated layout design in an industrial environment. (2016) - Ascheri, Andrea Egidio; Furini, Francesco; Colombo, Giorgio; Atzeni, Eleonora; Ippolito, Massimo
Technical knowledge and experience are intangible assets crucial for competitiveness. Knowledge is particularly important when it comes to complex design activities such as the configuration of manufacturing systems. The preliminary design of manufacturing systems is subject to a huge variability of inputs and outputs and involves decisions which must satisfy many competing requirements. This early engineering phase relies mostly on experience of designers and engineers and is associated with long lead times and high probability of mistakes. Knowledge-Based Engineering (KBE) and knowledge representation techniques are considered to be a successful way to tackle this design problem at an industrial level. This paper presents a methodology to support the configuration of powertrain assembly lines, reducing design times by introducing a best practice for production systems provider companies. The methodology is developed in a real industrial environment, introducing the role of a knowledge engineer. The approach includes extraction of existing technical knowledge and implementation in a knowledge-based software framework. The framework is then integrated with other software tools allowing the first phase design of the line including the line technical description and a 2D and 3D CAD line layout. The KBE application is developed and tested on a specific powertrain assembly case study for which existing knowledge is collected, formalised, implemented in the application and integrated with existing tools. Finally, the paper presents a first validation among design engineers, comparing traditional and new approaches and estimating a cost-benefit analysis useful for future possible KBE implementations.